WHO grade III gliomas: a 3-year institutional retrospective case series analysis of the correlation between IDH-1 mutation, Ki67 and progression free survival (2012-1015). (31st January 2018) - Kumar, Aditaya; Grivas, Athanasios
Abstract: OBJECTIVES: To assess the correlation between Ki67 proliferation index, IDH-1 mutation status and perform a subset analysis of progression free survival in World Health Organisation (WHO) Grade III gliomas DESIGN: A 3 year retrospective case series analysis. SUBJECTS: Patients newly diagnosed with pathological WHO grade III glioma 2012–2015. METHODS: Electronic interrogation of case notes in NHS Greater Glasgow & Clyde and Scottish National PACS. RESULTS: 44 patients (male:female ratio 1.2:1). Mean age was 52yrs (range: 20-74yrs). 63.6% were anaplastic astrocytomas, 18.2% anaplastoc oligodendrogliomas, 6.8% oligodendrogliomas, 9.1% were oligoastrocytoma and 2.3% were anaplastic pleomorphic xanthoastrocytoma. IDH-1 mutation occurred in 65.9% of patients. Ki67 ranged from 4–40 (IDH-1 wild type range: 4–40; IDH-1 mutated range: 6–40). Student's t-test showed no statistical significance between IDH-1 mutation status and Ki67 index (p=0.51). Progression free survival was assessed using the Kaplan-Meier method and log-rank test was used for comparison between groups defined by IDH-1 mutation status and high versus low Ki67 proliferation index (high Ki67 ≥ 20). Ki67 status was not significantly linked to progression free survival in patients with IDH-1 mutated disease (z=1.24, p=0.22); however patients with wild type IDH-1and high Ki67 had significantly shorter progression free survival than those with low Ki67 (z=2.15, p<0.05). CONCLUSIONS: Contrary to the published literature we find no correlation between IDH-1 mutation status and Ki67 in grade III glioma. Progression free survival is not significantly correlated with Ki67 status in IDH-1 mutated disease. Patients with wild type IDH-1 and high Ki67 have significantly shorter progression free survival than those with low Ki67.